2011
DOI: 10.2903/j.efsa.2011.2318
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on re‐evaluation of calcium carbonate (E 170) as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion re-evaluating the safety of calcium carbonate (E 170). Calcium carbonate is an inorganic salt authorised as a food additive in the EU, and is also included in the list of substances that may be added for specific nutritional purposes in foods for particular nutritional uses and in Directive 2002/46/EC relating to food supplements. Calcium carbonate was previously evaluated by JECFA in 1965, when the Committee establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Calcium oxide, calcium hydroxide, and calcium carbonate are considered safe for humans and the environment. These minerals are often used as a food additive ( Galvan-Ruiz, Banos & Rodriguez-Garcia, 2007 ; EFSA Panel on Food Additives & Nutrient Sources added to Food (ANS), 2011 ). Nonetheless, the total dietary calcium consumption from all sources should not exceed 2,000 mg/day ( Galvan-Ruiz, Banos & Rodriguez-Garcia, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium oxide, calcium hydroxide, and calcium carbonate are considered safe for humans and the environment. These minerals are often used as a food additive ( Galvan-Ruiz, Banos & Rodriguez-Garcia, 2007 ; EFSA Panel on Food Additives & Nutrient Sources added to Food (ANS), 2011 ). Nonetheless, the total dietary calcium consumption from all sources should not exceed 2,000 mg/day ( Galvan-Ruiz, Banos & Rodriguez-Garcia, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The acceptable daily intake has not been specified (thus, quantum satis is allowed), but some estimates indicate that exposures to calcium from all sources, including the use of calcium carbonate as a food additive, taken together with intakes of calcium from supplements and from fortified food should be below 2500 mg/day [89]. Thus, considering the trace levels of calcium carbonate used as food additives, there is no evidence of toxicity or carcinogenic effects [89]. In fact, calcium carbonate has a relevant physiological role in the human body, participating in blood coagulation processes, ensuring constant osmotic blood pressure and regulating various intracellular processes.…”
Section: Calcium Carbonatementioning
confidence: 99%
“…21, calcium salts of carbonic acid). Calcium carbonate is also authorised as food additive (E 170) and was re‐evaluated by the ANS Panel in 2011 (EFSA ANS Panel, 2011 ). In its evaluation, the ANS Panel agreed with the group ADI ‘not specified’ assigned by SCF to a group of carbonates, including calcium carbonate, when considering the use of calcium carbonate as a food additive.…”
Section: Assessmentmentioning
confidence: 99%
“…42500) in the SCF list 1 with an ADI ‘not specified for carbonate’. Moreover, the ANS Panel re‐evaluated CaCO 3 (E 170) as a food additive in 2011 (EFSA ANS Panel, 2011 ). In its evaluation that included some of the data submitted in this application, the ANS Panel concluded that ‘trace levels of adventitious nanoscale material within macroscale calcium carbonate are not of toxicological concern’ and agreed with the group ADI ‘not specified’ assigned by the SCF to a group of carbonates including calcium carbonate used as a food additive.…”
Section: Assessmentmentioning
confidence: 99%